(untitled) (CAHIERS MAGELLANES-NS, 2024)
Many studies have been done on the causes and remedies of Segregation in Concrete. Water to cement ratio is the major reason behind the causes of segregation. Cement content, size and surface texture of aggregates, percentage of admixtures, transportation and compaction are other factors for causes of segregation. In this research, how water to cement ratio (W/C) and size of coarse aggregate affect the chances of segregation in concrete have been done. Water to cement ratio varies from 0.4 to 0.6 in this study. Also, size of coarse aggregate varied with different proportions. From test result received and analyzed from segregation test setup it was found the possibility of segregation increased if the water to cement ratio is more than 0.50. Also, the results were compared with slump test as per Indian codal provisions.